The Effectiveness of Islamic Work Value on Medical Career Planning Web Application for Analysis Anticipated Work-Family Conflict - Rahayuningsih, Tri; Indra, Zul; Febtriko, Anip; Adi Putra, Ardian; Nesyia Nasution, Itto; Anggraini, Rini; Hartati, Rini (International Journal of Engineering and Technology, 2018)
The dynamics of medical education continue to innovate and specialized, it requires the graduates to choose a career well. They should not only consideration of ability, but also could manage roles for responsibilities at work and family in future. Career planning in Bandura's Social Cognitive Theory includes personal value factors, which in this study are Islamic work values (IWV). Decisions on career choices can be strengthened by looking at the factors of anticipated work-family conflict (AWFC). Therefore, expert knowledge is used as a rule for web-based assessment and forecasting factors that could reduce conflict in the future. This study aimed to assist career development in the field of medicine in determine the priority role of work-family, by identified risk factors for possible anticipated work-family conflict based on Islamic work value, so that it could be taken decisions on career options using an expert systems. This research would be useful for psychology theoretically, as well as the used of information technology related to work-family conflict in web application. The result is SICES - AWFC software that is able to diagnose work-family conflicts (WFC) in the future and help medical students for career planning by considered Islamic work values.Â